Clinical efficacy and tolerability of mometasone furoate nasal spray in perennial allergic rhinitis patients : an open multicentre study (Faculty of Medicine Universitas Indonesia, 2002)
Mometasone furoate (MF) aqueous nasal spray has been shown to be effective and well-tolerated in the treatment of perennial allergicÂ rhinitis (PAR). All of the sudies, however, have been conducted in Canada, UK, and Europe. Therefore, a bridging study is warranted inÂ view of the different climatic conditions in tropical countries. To evaluate the clinical efficacy and tolerability of MF aqueous nasal spray inÂ the treatment of PAR in a tropical country. This study was an open, non comparative, 4-week 3-centre trial in outpatients of 12 to 60 yearsÂ with moderate to severe PAR of at least 2 years duration. Patients were allergic to at least one major PAR allergen, confirmed by skin prickÂ test. They had total nasal symptom score (TNSS) of â¥Â 6 and nasal congestion score (NCS) of â¥Â 2 on â¥Â 3 diary time points prior to baselineÂ visit and at both screening and baseline visits. Eligible patients received MF aqueous nasal spray at baseline visit, and administered 200 ÂµgÂ mometasone every morning for 4 weeks. The primary clinical efficacy parameter was the mean percentage reduction of TNSS fromÂ baseline. Of 100 eligible patients, all completed this 4-week trial. The patient-evaluated TNSS (sum of the Last 3 mornings) decreasedÂ signiftcantly from baseline with a mean reduction of 60.9 % (p < 0.0001,) at week-2 and 73.6 % (p < 0.0001) at week-4. The meanÂ reductions in physician-rated TNSS (61.7 % at week-2 and 77.8 % at week-4) were higher than those in the previous studies (43 % and 51Â % at week-2, 52 % and 54 % at week-4). Similar trends were observed for nasal congestion score (NCS), other individual symptoms, totalÂ symptoms, and clinical efficacy rates. Evening symptoms were reduced similarly as morning symptoms There was no withdrawal due toÂ adverse event. MF aqueous nasal spray, at a dose of 200 Âµg once daily in the morning for the treatment of moderate to severe PAR in aÂ tropical country, was clinically effective with 24-hour control of PAR symptoms, and was well tolerated. (Med J Indones 2002; 11: 69-80)Keywords : mometasone furoate, nasal spray, perennial allergic rhinitis.